2011
DOI: 10.1002/app.33712
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of bone cement using nanoparticle: The effect of solvent

Abstract: Drawbacks of poly(methyl methacrylate) (PMMA)-based bone cement as a grouting agent for in vivo fixation of orthopedic and dental implants such as considerable low mechanical strength have been improved using nanotechnology. Bone cement-layered silicate nanocomposites have been prepared without any heat treatment in the presence of polar (dimethyl formamide, DMF) and nonpolar (benzene) solvents. Solvents have been removed completely from the bone cement after its preparation. Nanostructure is very much depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…However, such kind of PMMA/MMT nanocomposites reported in the open literature so far were mainly prepared by simply adding MMT clays into commercially available suspension polymerized PMMA through melt intercalation or during curing process , yet the studies of PMMA/MMT nanocomposites prepared by in situ suspension polymerization are scarcely reported. In 2001, Huang et al first reported the synthesis of PMMA/MMT nanocomposites by in situ suspension polymerization and an improvement of thermal stability was observed .…”
Section: Introductionmentioning
confidence: 99%
“…However, such kind of PMMA/MMT nanocomposites reported in the open literature so far were mainly prepared by simply adding MMT clays into commercially available suspension polymerized PMMA through melt intercalation or during curing process , yet the studies of PMMA/MMT nanocomposites prepared by in situ suspension polymerization are scarcely reported. In 2001, Huang et al first reported the synthesis of PMMA/MMT nanocomposites by in situ suspension polymerization and an improvement of thermal stability was observed .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The application of a nanotextured material may reduce the risk of implant failure by improving osseo-integration. 7,15,25,26,29 Mature bone has an inorganic mineral size of roughly 50 nm × 25 nm × 4 nm, which represents a coarse surface in nanometric terms. 8,30 In contrast, modern orthopaedic implant surfaces are smooth at the nanometric level.…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%
“…However, the BC poses some significant limitations such as high exothermic temperature (>70°C), fatigue failures, aspetic loosening, and predominant residual free radicals toxicity, which are generated during the in situ polymerization. (He et al, ; Jaiswal et al, ; Kapusetti et al, ; Lewis & Ed, ; Lopez‐Heredia et al, ; Marrs, Andrews, Rantell, & Pienkowski, ; Misra, Kapusetti, Jaiswal, & Maiti, ; Nussbaum, Gailloud, & Murphy, ; Vaishya, Chauhan, & Vaish, ) The exothermic polymerization of BC is processed by radical‐initiated chain growth reactions (He et al, ). During polymerization, the DMPT breaks down and interacts with BPO to form phenyl radical and attacks the double bond of the MMA monomer and leads further polymerization process (Jaiswal et al, ; Lewis & Ed, ; Nussbaum et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During polymerization, the DMPT breaks down and interacts with BPO to form phenyl radical and attacks the double bond of the MMA monomer and leads further polymerization process (Jaiswal et al, 2015;Lewis & Ed, 1994;Nussbaum et al, 2004). Benzoyl and benzoate are the free radicals generated in the above reaction from BPO and DMPT, respectively (Misra et al, 2011). It is well recognized that the presence of residual free radical followed by the in situ polymerization is the main culprits for significant toxicity effects (Graham, Pruitt, Ries, & Gundiah, 2000;Kapusetti et al, 2013;Lopez-Heredia et al, 2012;Marrs et al, 2006).…”
mentioning
confidence: 99%